Are lighter-skinned Tanisha and Jamal worth more pay? White people's gendered colorism toward Black job applicants with racialized names. Issue 5 (4th April 2022) - Stockstill, Casey; Carson, Grace
ABSTRACT: Though race is complex in lived experience, studies of anti-Black prejudice and discrimination in the United States often elide this complexity by operationalizing "Black" using one racial marker. We consider how three intersecting markers – skin colour, names, and gender – predict white people's anti-Black prejudice. Using two experiments where white participants evaluated fictitious job applicants, we randomly manipulated the applicant's name (distinctly Black or indistinctly Black) and race/skin colour (white, lighter-skinned Black, medium-skinned Black, or darker-skinned Black). We predicted that when women and men targets had distinctly Black names or darker skin, they would be rated more negatively. Results suggest gendered colorism via salary recommendations, where participants offered a darker-skinned man with a distinctly Black name less salary. However, a darker-skinned woman with a distinctly Black name was offered more salary. We argue that anti-Black prejudice may take on nuanced and gendered forms in the twenty-first century.